Integration of Ethnomathematics Mandar Tribe for Elementary School Mathematics Materials - Eka Wahyuni; Suherman Suherman; Tri Surianingsih; Ismaya Ismaya; Elihami Elihami (Universitas Muhammadiyah Enrekang, 2023)
The purpose of this study is to describe the integration of ethnomathematics in the culture of the Mandar tribal community in Polewali Mandar Regency and Majene Regency in elementary mathematics teaching material supplements. This qualitative research uses research with an ethnographic approach. The ethnomathematics obtained relates to elementary mathematics materials, among others, namely, Addition and Subtraction of numerical numbers up to 99, Simple Flat Buildings and Simple Spaces, Simple Fractions, Length of Time of an Event (unit of time), Multiples of a Number and Multiples of Communal Numbers, Folding Symmetry and Rotary Symmetry, Nonstandard Measurements (units of length, units of content, units of weight), Perimeter of Flat Buildings (Square, Long Square, and Triangle), Presentation of Data, Position of Objects Against the Wind.